Current applications of drug delivery nanosystems associated with antimicrobial photodynamic therapy for oral infections - Silvestre, Amanda Letícia Polli [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Besegato, João Felipe [UNESP]; de Annunzio, Sarah Raquel [UNESP]; Almeida Furquim de Camargo, Bruna [UNESP]; de Melo, Priscila Borges Gobbo [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Fontana, Carla Raquel [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2021)
The oral cavity is colonized by several species of microorganisms that can cause dental caries, periodontal diseases, candidiasis, endodontic infections, and, among other diseases related to the dental field. Conventional treatment consists of mechanical removal associated with systemic administration of antimicrobials, which can cause various side effects and microbial resistance. In this context, alternative therapies have been developed, including Antimicrobial Photodynamic Therapy (aPDT). For the improvement of therapy, the implementation of nanotechnology is very important to optimize the delivery system of the dyes or photosensitizers on biological targets. Besides, this combination provides a non-invasive treatment, better solubility and bioavailability, delivery to the target site, controlled release and protection against external and physical–chemical factors, low side effects, and, unlikely resistant species. Although, there are numerous researches on aPDT and nanotechnology, few review articles based on the combination of these three aspects: nanosystems, aPDT and oral infections are available. For this reason, this article aims to discuss the advances and advantages of this combination. Therefore, this article was divided into different types of nanosystems (organic and inorganic nanoparticles) associated with aPDT bringing a description of it is definitions, properties, and, applications in oral infections.
Keywords: aPDT; Dental field; Drug delivery; Nanoparticles; Oral infections; Review